Targeting MCF-7 Cell Line by Listeriolysin O Pore Forming Toxin Fusion with AHNP Targeted Peptide - Fotoohi-Ardakani, Gholamreza; Kheirollahi, Majid; Zarei Jaliani, Hossein; Noorian, Mohadese; Ansariniyia, Hossein (Advanced biomedical research, 2019)
Tumor-targeting peptides are attracting subjects in cancer therapy. These peptides, which are widely studied, deliver therapeutic agents to the specific sites of tumors. In this study, we produced a new form of recombinant listeriolysin O (LLO) with genetically fused Anti-HER2/neu peptide (AHNP) sequence adding to its C-terminal end. The aim of the study was to engineer this pore-forming toxin to make it much more specific to tumor cells. Two forms of the toxin (with and without peptide) were subcloned into a bacterial expression plasmid. Subcloning was performed using a polymerase chain reaction (PCR) product as a megaprimer in a quick-change PCR to introduce the whole insert gene into the expression plasmid. After expression of two recombinant forms of LLO in BL21 DE3 cells, purification was performed using Ni-NTA affinity column. MDA-MB-231 and MCF-7 cell lines (as negative and positive controls, respectively) were treated with both LLO toxins to evaluate their cytotoxicity and specificity. The IC of LLO on MDA-MB-231 and MCF-7 cells was 21 and 5 ng/ml, respectively. In addition, IC for the fusion AHNP-LLO toxin was 140 and 60 ng/ml, respectively. It was found that the cytotoxicity of the new engineered AHNP-LLO toxin has decreased by about 9x compared to the wild-type toxin and the specificity of the AHNP-LLO toxin has been also reduced. Results show that the C-terminal of the LLO should not be modified and it seems that N-terminal of the toxin should be preferred for engineering and adding peptide modules.